Geoengineering tensions. (September 2018) - Currie, Adrian
Highlights: The relationship between measures to govern geoengineering should be understood in terms of effects on scientific incentives. Decoupling geoengineering research from deployment turns on questions scientists are not qualified to answer, or factors outside of their control. Governance relating to geoengineering must be sensitive to the need for governance to extend beyond the traditional boundaries of scientific research itself. Abstract: There has been much discussion of the moral, legal and prudential implications of geoengineering, and of governance structures for both the research and deployment of such technologies. However, insufficient attention has been paid to how such measures might affect geoengineering in terms of the incentive structures which underwrite scientific progress. There is a tension between the features that make science productive, and the need to govern geoengineering research, which has thus far gone underappreciated. I emphasize how geoengineering research requires governance which reaches beyond science's traditional boundaries, and moreover requires knowledge which itself reaches beyond what we traditionally expect scientists to know about. How we govern emerging technologies should be sensitive to the incentive structures which drive science.